Empowerment of The Few and Disempowerment of The Many - Disempowerment in Thai ‘One Tambon One Product' Organizations (OTOPS) - Diefenbach, Thomas (The South East Asian Journal of Management, 2016)
Thai ‘One Tambon One Product’ organisations (OTOPs) have had considerable economic suc-cess since their initiation by the Thai government in 2001. However, in contrast to their ever-increasing economic relevance, OTOPs’ contributions to social development have been acknowl-edged and interrogated only very little. In particular the issue of empowerment, a key component of any social development whether within organisations, at community or even societal level, is strangely absent from any discourse about OTOPs. This article looks at how far the idea of em-powerment is realised within Thai OTOPs – or how far it is not realised. For this, a three-dimensional concept of empowerment has been developed and applied. The data show a rather mixed picture with regard to empowerment; only some people are empowered whereas many others are systematically disempowered. OTOPs seem to contribute to quite some extent to the further strengthening of existing patterns of social dominance, stratification and inequalities.